2016
DOI: 10.1080/00140139.2016.1206624
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 12.8-km military load carriage activity on lower limb gait mechanics and muscle activity

Abstract: The high stress fracture occurrence in military populations has been associated with frequent load carriage activities. This study aimed to assess the influence of load carriage and of completing a load carriage training activity on gait characteristics. Practitioner Summary:This study identified gait changes due to load carriage and after a military load carriage training activity. Such activities are associated with lower limb stress fractures. A prepost study design was used. Gait mechanics changed to a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…It is therefore unclear whether a longer ground contact time is associated with the development of injury, or if it is a mechanism to minimize the risk of injury. Therefore, interventions for increasing muscular strength and endurance of the plantar flexor and knee extensor muscles may be beneficial [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore unclear whether a longer ground contact time is associated with the development of injury, or if it is a mechanism to minimize the risk of injury. Therefore, interventions for increasing muscular strength and endurance of the plantar flexor and knee extensor muscles may be beneficial [2].…”
Section: Discussionmentioning
confidence: 99%
“…Regular load carriages are criteria risk factors for Muscular Skeletal Disorders (MSDs) in hikers, backpackers, and soldiers [1,2]. The prevalence of MSDs is significantly related to the weight and mode of carrying a backpack among the load carrying population [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both vertical and sagittal ground reaction force increase with the presence of body borne load, with peak ground reaction force increasing significantly at as low as a 20 kg load, resulting in changes up the kinetic chain [13][14][15][17][18][19] . Previous studies have shown mixed results regarding the range of motion of sagittal plane knee range of motion while walking with body borne load, but knee flexion has consistently been shown to increase with the addition of body borne load to help stabilize the knee 7,[12][13][14]18,19,22,[56][57][58] . In order to stabilize the knee, knee flexion helps the body lower the center of mass, but this also increases the forces and torques on the knee, increasing loading on the soft tissues at the knee 7,12,[14][15][16]18 .…”
Section: Effects On Knee and Ground Reaction Forcesmentioning
confidence: 99%
“…As fatigue increases, stride time and length decrease, and ground contact time and step width variability increases 31,58,69 . While these alterations help stabilize the body, these are factors that indicate a decrease in stability during muscular fatigue.…”
Section: Effects On Lower Limbmentioning
confidence: 99%
See 1 more Smart Citation